2018
DOI: 10.1103/physrevb.97.020403
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the magnetic proximity effect on spin-orbit torque efficiencies in ferromagnet/platinum bilayers

Abstract: Current-induced spin-orbit torques in Co 2 FeAl/Pt ultrathin bilayers are studied using a magnetoresistive harmonic response technique, which distinguishes the dampinglike and fieldlike contributions. The presence of a temperature-dependent magnetic proximity effect is observed through the anomalous Hall and anisotropic magnetoresistances, which are enhanced at low temperatures for thin platinum thicknesses. The fieldlike torque efficiency decreases steadily as the temperature is lowered for all Pt thicknesses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…For this study, the Co layers were wedges with thickness varying between 0.75 and 1.4 nm for x = 1 and between 0.64 and 0.94 nm for x ≤ 0.75 across the wafer to enable the study of both PMA and IMA Pd 1− x Pt x /Co devices. For Pd 1− x Pt x /Co bilayers, the saturation magnetization ( M s ) varies between 1450 and 1700 emu cm −3 for different x , indicative of an enhancement due to a magnetic proximity effect at the interface, which, however, should not degrade ξ DL as is discussed previously . M s for the Pd 1− x Pt x /Fe 0.6 Co 0.2 B 0.2 bilayers remains almost constant with x , ≈1200 emu cm −3 .…”
Section: Resultssupporting
confidence: 78%
“…For this study, the Co layers were wedges with thickness varying between 0.75 and 1.4 nm for x = 1 and between 0.64 and 0.94 nm for x ≤ 0.75 across the wafer to enable the study of both PMA and IMA Pd 1− x Pt x /Co devices. For Pd 1− x Pt x /Co bilayers, the saturation magnetization ( M s ) varies between 1450 and 1700 emu cm −3 for different x , indicative of an enhancement due to a magnetic proximity effect at the interface, which, however, should not degrade ξ DL as is discussed previously . M s for the Pd 1− x Pt x /Fe 0.6 Co 0.2 B 0.2 bilayers remains almost constant with x , ≈1200 emu cm −3 .…”
Section: Resultssupporting
confidence: 78%
“…Experimental works, however, seem to confirm the possible Rashba-Edelstein origin of the field. 31,32 Note, that an interfacial contribution might be also attributed to magnetic proximity effect from ferromagnet, 33,34 which was recently discussed by Zhu et al 35 The authors showed that proximity effect in Co/Pt and Au 25 Pt 75 /Co interfaces has minimal correlation on either the dampinglike or the fieldlike spin-orbit torques compared to other interfacial effects like interfacial spin-orbit scattering. The relevant parameters used to modelled of the effective fields are summarized in Table I.…”
Section: Resultsmentioning
confidence: 93%
“…Earlier studies have shown that the structural properties of the atoms near the FM/NM interface determine the spin-transport properties [17,18]. Furthermore, broken spatial inversion symmetry at the FM-NM interface can be attributed to nonequivalent spin-transport properties (e.g., SOT, iDMI) [19][20][21][22] between NM/FM (FM on top of NM) and FM/NM (NM on top of FM). Earlier studies showed that in symmetric * anil@iisc.ac.in NM/FM/NM systems, SOT and iDMI can prevail due to different structural and/or magnetic properties at the NM/FM and FM/NM interfaces.…”
Section: Introductionmentioning
confidence: 99%